Projeto de uma estação de tratamento de água usando Filtração em Múltiplas Etapas (FiME) para o Assentamento Rural Bela Vista Paranapanema-SP adaptado às demandas dos assentados - Lisboa, Pedro Roberto Araújo (Universidade Federal de São Carlos, 2025)
This work is the result of a partnership between the Federal University of São Carlos (UFSCar), mediated by the Center for Extension and Research in Water and Effluents (CEPAE), and the management of the Bela Vista Paranapanema-SP Rural Settlement. The settlement has no access to drinking water and the water treatment model suggested in the project is based on the characterization of the raw water from the Jurumirim Dam and is adapted to the demands raised by the community through assemblies. The Water Treatment Plant (WTP) model suggested is Multi-stage Filtration using water tanks as a tank and includes the stages of dynamic pre-filtration in pebbles, vertical upward flow pre-filtration in pebbles and sand and slow filtration with fine sand, activated carbon and two synthetic blankets. In order to adapt to the demands, the raw and treated water pumping stations were sized and the tanks were resized for masonry construction.
Design of a Water Treatment Plant Using Multi-Stage Filtration (FiME) for the Bela Vista Rural Settlement in Paranapanema-SP, adapted to the settlers' needs.
Keywords: Tratamento de água; Água potável; Saneamento rural; Filtração lenta; Troca de saberes; Assentamento; FiME; Drinking water; Rural sanitation; Slow filtration; Exchange of knowledge; Settlement; Filtration in multiple steps; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS